Effect of written corrective feedback in research writing competence of non-education students (Educational Dimension, 2024)
This research addressed several key problems: the extent of use of teachers' feedback strategies, the effects of WCF on students' performance, and the significant correlation among the variables. A quantitative descriptive research design was used, and 153 participants were surveyed through the messenger platform and Google Forms. Research findings indicate that among the four types of written corrective feedback (WCF), direct feedback was the most frequently employed strategy by teachers, while focused feedback was the least utilised. Furthermore, results indicate that students value reflective learning facilitated by teachers' written corrective feedback, especially in error recognition and constructive feedback responses, as non-education students displayed positive attitudes toward receiving feedback. The study also revealed a positive correlation between WCF and research writing performance, regardless of age, gender, or degree program, with relatively low values at 0.022, 0.003, and 0.005, respectively, using partial eta squared. Additionally, significant correlations were observed between students' GPAs in research courses and the impact of WCF, revealing a disparity in GPAs between Research 1 and Research 2. As direct, unfocused, and indirect written corrective feedback showed a statistically significant relationship in the extent of use of teachers' written corrective feedback, focused feedback shows no significant correlation. The findings emphasise the importance of evaluating different written corrective feedback strategies to enhance students' research writing outcomes. Findings call for the strategic use of written corrective feedback based on the specified needs and level of performance of non-education students. Furthermore, students, teachers, and the institution are to work hand in hand to create a culture of continuous improvement of students in research writing and academic performance through written corrective feedback.
Keywords: written corrective feedback; research writing; non-education students